2011
DOI: 10.1093/humrep/der378
|View full text |Cite
|
Sign up to set email alerts
|

Effect of infertility treatment and pregnancy-related hormones on breast cell proliferation in vitro

Abstract: background: Breast cancer development involves a series of mutations in a heterogeneous group of proto-oncogenes/tumor suppressor genes that alter mammary cells to create a microenvironment permissive to tumorigenesis. Exposure to hormones during infertility treatment may have a mutagenic effect on normal mammary epithelial cells, high-risk breast lesions and early-stage breast cancers. Our goal was to understand the association between infertility treatment and normal and cancerous breast cell proliferation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…35,36 In 2 recent in vitro studies, FSH, luteinizing hormone, and clomiphene did not increase breast cell proliferation, whereas estrogen increased cell proliferation of estrogen receptor-positive breast cancer cells. 37,38 Progesterone and hCG both decreased breast cell proliferation. 38 A case-control study reported a decreased risk of breast cancer after hCG given during infertility or weight loss treatments.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…35,36 In 2 recent in vitro studies, FSH, luteinizing hormone, and clomiphene did not increase breast cell proliferation, whereas estrogen increased cell proliferation of estrogen receptor-positive breast cancer cells. 37,38 Progesterone and hCG both decreased breast cell proliferation. 38 A case-control study reported a decreased risk of breast cancer after hCG given during infertility or weight loss treatments.…”
Section: Discussionmentioning
confidence: 98%
“…37,38 Progesterone and hCG both decreased breast cell proliferation. 38 A case-control study reported a decreased risk of breast cancer after hCG given during infertility or weight loss treatments. 39 In our study, women with the highest number of IVF cycles had the lowest risk of breast cancer.…”
Section: Discussionmentioning
confidence: 98%
“…11,12 Breast cancer cells and tumors respond to progestins through an unknown mechanism, which generally act as pro-survival and proliferative factors. 7,[13][14][15][16][17] Progestins may also promote angiogenesis and assist in immunoevasion, both of which contribute to tumor survival and growth.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, increased production of estrogens during infertility treatment may promote the malignant potential of key cell cycle regulatory proteins in mammary epithelium (15). Our prior work showed no effect of E2 on ER− MCF-10A and HCC 1937 cells in vitro, with doses of E2 comparable to those observed during COH cycles, whereas an expected increase in proliferation was observed when MCF-7 ER+ cells were treated with escalating does of estrogen (16,17). For breast cancer patients with ER+ lesions, the proliferative effect of E2 on malignant cells is well established.…”
Section: Discussionmentioning
confidence: 76%
“…Estradiol (E2), a known cell cycle mitogen and promoter of breast cell proliferation (1315), is elevated to supraphysiologic levels during COH for IVF. Previous work assessing the effects of E2 in estrogen receptor-positive (ER+) breast cancer cells in vitro showed a proliferative effect at treatment levels similar to those encountered during IVF cycles (16). Furthermore, escalating doses of E2 correlated with increased ER+ breast cancer cell proliferation.…”
Section: Introductionmentioning
confidence: 91%